Sleep and sleepiness in shift-working tram drivers. (October 2020) - Onninen, Jussi; Hakola, Tarja; Puttonen, Sampsa; Tolvanen, Asko; Virkkala, Jussi; Sallinen, Mikael
Abstract: Driver sleepiness contributes to traffic accidents. However, sleepiness in urban public transport remains an understudied subject. To fill this gap, we examined the sleepiness, sleep, and on-duty sleepiness countermeasures (SCMs) in 23 tram drivers working morning, day, and evening shifts for three weeks. Sleepiness was measured using Karolinska Sleepiness Scale (KSS). Nocturnal total sleep time (TST) was measured with wrist actigraphy. SCMs and naps were self-reported with a smartphone application. Caffeine and napping were considered effective SCMs. Severe sleepiness (KSS ≥ 7) was observed in 22% of shifts with no differences between shift types. Rest breaks were associated with slight reductions in sleepiness. TST between days off averaged 7 h but was 1 h 33 min and 38 min shorter prior to morning and day shifts, respectively. The use of effective SCMs showed little variance between shift types. These results highlight the need for fatigue management in non-night-working tram drivers. Highlights: Tram drivers experience severe sleepiness in over one-fifth of non-night shifts. Sleep prior to morning and day shifts is shorter than generally recommended. Effective sleepiness countermeasures such as napping and caffeine not widely used. Fatigue management might benefit driver alertness, lowering accident risk.